Comparison of the Vowel Formant Measurements in Karo and Simalungun Language - Br Sembiring, Franinta Egia D. R; Tengku Syarfina; Sekar Azzahra (JADEs Journal of Academia in English Education, 2024)
The study aims to discuss the vowel formant of the Karo and Simalungun languages. This study uses qualitative methods with the data described as numeric tables. In collecting data, the researcher involved three native speakers from both sides. The native speakers are three females from the Karo and Simalungun areas between 17 and 45 years old. The data was obtained by recording in a convenient location, and the syllables were naturally uttered. This study found that the Karo language has six vowels such as /a/, /i/, /u/, /e/, /É™/, and /É”/, and is similar to the Simalungun language except vowel /É™/. To compare the vowels, the researcher placed similar vowels to compare the form between both languages. The syllables's position, /a/, /i/, /u/, and /e/, is put at the beginning to make the syllable manageable, and the syllable /É”/ is placed at the end of the word. This study uses the software Praat to measure the vowel formant. Afterward, the data are calculated using the F1 and F2 from the spectrogram in Praat software. The results data shows that the highest formant in vowel /a/, /i/, /u/, and /e/ comes from KL, and the highest vowel /É”/ from SL.